2021
DOI: 10.1039/d1py00713k
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of furan-based poly(ester amide)s: an investigation of crystallization, molecular dynamics and degradation kinetics of novel poly(ester amide)s based on renewable poly(propylene furanoate)

Abstract: Ιn this work novel polyester amides (PEAs) based on biobased poly(propylene furanoate) (PPF) were synthesized via traditional melt polycondensation, utilizing a preformed symmetric amido diol (AD) containing two internal amide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…Generally, furan rings had two different effects on the T g of PA10T/10Fs. On the one hand, the introduction of furan rings reduced the intermolecular hydrogen bonding, 23,40,41 as confirmed by the DFT calculation, and could also reduce the regularity of the molecular chains, which led to the decrease of the degree of crystallinity, resulting in the decrease of T g . 45 On the other hand, the hindrance in furan ring flipping increased the rigidity of the molecular chain, and the nonoverlap of positive and negative charge centers of the furan ring brought a permanent dipole moment, which increased molecular chain rigidity, resulting in a higher T g .…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Generally, furan rings had two different effects on the T g of PA10T/10Fs. On the one hand, the introduction of furan rings reduced the intermolecular hydrogen bonding, 23,40,41 as confirmed by the DFT calculation, and could also reduce the regularity of the molecular chains, which led to the decrease of the degree of crystallinity, resulting in the decrease of T g . 45 On the other hand, the hindrance in furan ring flipping increased the rigidity of the molecular chain, and the nonoverlap of positive and negative charge centers of the furan ring brought a permanent dipole moment, which increased molecular chain rigidity, resulting in a higher T g .…”
mentioning
confidence: 70%
“…For polyamides, the strong influence of hydrogen bonds determines the structure–property–performance relationship of synthetic polyamides. It was found that the oxygen heteroatom in the FDCA ring acts as a hydrogen bond acceptor to form intramolecular hydrogen bonds, and those impede the formation of intermolecular hydrogen bonds and interaction forces that are the main crystallization forces in polyamides. ,, Hence, it is necessary to investigate the intermolecular and intramolecular hydrogen bonds for PA10T/10Fs. DFT was used to calculate the bond energies of the intermolecular and intramolecular hydrogen bonds for PA10T and PA10F through the optimization of the structures of the dimer structures, folding conformations, and straight chain conformations.…”
Section: Resultsmentioning
confidence: 99%
“…Most polymers are based on petrochemicals, but the increasing environmental awareness and dwindling fossil fuel resources have made it clear that this needs to be changed. Consequently, there is a growing interest in the use of renewable raw materials for fuels, chemicals, and polymer materials [ 1 ]. In 2004, the US Department of Energy recognized 2,5-furanedicarboxylic acid (FDCA) as one of the twelve most important renewable materials [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FDCA and its derivatives find application in the synthesis of bio-based polyurethanes, polyamides, and especially polyesters. The similar structure of FDCA to terephthalic acid (TPA) popularized the synthesis of materials such as poly(ethylene 2,5-furanoate) (PEF) and poly(propylene furanoate) (PPF), which are more environmentally friendly equivalents of poly(ethylene terephthalate) (PET) and poly(propylene terephthalate) (PPT) [ 1 , 3 , 4 ]. Moreover, due to the heteroatom in the structure of the furan ring, polyesters based on FDCA exhibit excellent gas barrier properties [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation